Corporate Value Estimation of PT Sri Rejeki Isman Tbk - Nugroho, Fajar; Damayanti, Sylviana Maya (Journal of Business and Management, 2015)
Abstract. Indonesia has the second largest export market share among Southeast Asia Region on textile exports which is 28.5% or 4.6 billion US dollar and 18.3% or 7.7 billion US dollar on garment exports. One of the biggest textile and garment factories is PT Sri Rejeki Isman Tbk. PT Sri Rejeki Isman Tbk had strategy to expand its business in the following year. The strategies will drive greater sales with the consequences that expenses go up as well. The Company needs to do corporate valuation due to know the company share price so the company can choose the appropriate strategy to expand the business.The valuation methods used in this research are Asset based method, Market approach, and Discounted Cash Flow valuation. The outcome of this research is that the share price of PT Sri Rejeki Isman Tbk is undervalued based on valuation method. The assets-based approach showed the book value price per share is US$ 0.0158 (IDR 195.99). Market based approach showed the book value price per share is US$ 0.0131 (IDR 162.91). Comparing to the current market value price per share at the end of 2014, which is IDR 163, the stock performance is undervalue. And also based on Discounted Cash Flow method, the market price is undervalued. PT Sri Rejeki Isman Tbk, should increase the free cash flow and decreasing the cost of capital. PT Sritex should increasing the operating income and/or decreasing change in net working capital and net capital expenditure.Â Keywords: valuation, company valuation, textile, garment, share price, discounted cash flow, asset based approach, market approach